Football training improves metabolic and cardiovascular health status in 55‐ to 70‐year‐old women and men with prediabetes. (2nd May 2018) - Skoradal, M.‐B.; Weihe, P.; Patursson, P.; Mortensen, J.; Connolly, L.; Krustrup, P.; Mohr, M.
Abstract : We examined the effects of 16 weeks of football training and dietary advice on blood glucose control and health status in 55‐ to 70‐year‐old women and men with prediabetes. Fifty participants with prediabetes (age; 61 ± 6 years, BMI; 29.6 ± 4.7; VO2max 22.3 ± 5.7 mL·min −1 ·kg −1 ) were randomized into a football and dietary advice group (F+D; n = 27) and a dietary advice group (D; n = 23). F+D performed football training (twice weekly 30‐ to 60‐minutes sessions) and received dietary advice, while D only received dietary advice. An oral glucose tolerance test (OGTT) was completed pre and post the 16‐week period. Body composition, blood pressure, and maximal oxygen uptake (VO2max ) were additionally measured. Both groups demonstrated a decrement ( P  <   .05) in fasting blood glucose (−0.4 ± 0.5 mmol·L −1 ) and lowered blood glucose throughout OGTT. F+D displayed lower values than D ( P  <   .05) after 60 minutes (9.0 ± 2.7 vs 10.6 ± 2.9 mmol·L −1 ) and 120 minutes (5.7 ± 1.6 vs 7.5 ± 2.4 mmol·L −1 ). VO2max increased by 14% in F+D, with a higher ( P  <   .05) change score than in D (2%). Mean arterial pressure declined more ( P  <   .05) in F+D than in D (−8 ± 9 vs −4 ± 11 mm Hg). Fat loss was greater ( P  <   .05) in F+D than in D (−3.4 ± 2.8 vs −1.2 ± 2.0 kg), and the increase in lean body mass was also greater ( P  <   .05) in F+D than in D (0.7 ± 1.5 vs −0.3 ± 1.6 kg). In conclusion, football training combined with dietary advice has broad‐spectrum effects on metabolic and cardiovascular health profile with greater overall effects than professional dietary advice per se for 55‐ to 70‐year‐old women and men with prediabetes.